CRISPR/Cas9 Mediated Genome Engineering for Improvement of Horticultural Crops - Karkute, Suhas G.; Singh, Achuit K.; Gupta, Om P.; Singh, Prabhakar M.; Singh, Bijendra (Frontiers in Plant Science, 2017)
Horticultural crops are an important part of agriculture for food as well as nutritional security. However, several pests and diseases along with adverse abiotic environmental factors poses a severe threat to these crops by affecting their quality and productivity. This warrants the effective and accelerated breeding programmes by utilizing innovative biotechnological tools that can tackle aforementioned issues. The recent technique of genome editing by Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR associated 9 (CRISPR/Cas9) has greatly advanced the breeding for crop improvement due to its simplicity and high efficiency over other nucleases such as Zinc Finger Nucleases and Transcription Activator Like Effector Nucleases. CRISPR/Cas9 tool contains a non-specific Cas9 nuclease and a single guide RNA that directs Cas9 to the specific genomic location creating double strand breaks and subsequent repair process creates insertion or deletion mutations. This is currently the widely adopted tool for reverse genetics, and crop improvement in large number of agricultural crops. The use of CRISPR/Cas9 in horticultural crops is limited to few crops due to lack of availability of regeneration protocols and sufficient sequence information in many horticultural crops. In this review, the present status of applicability of CRISPR/Cas9 in horticultural crops was discussed along with the challenges and future potential for possible improvement of these crops for their yield, quality and resistance to biotic and abiotic stress